1992
DOI: 10.1172/jci115876
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation in volunteers of a candidate live oral attenuated Salmonella typhi vector vaccine.

Abstract: Clin. Invest. 1992. 90:412-420.)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
50
2

Year Published

1996
1996
2012
2012

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 83 publications
(53 citation statements)
references
References 45 publications
1
50
2
Order By: Relevance
“…There was no evidence for systemic spread of ZH9, since bacteria were not detected in the blood at any time. Serovar Typhi Ty2 aro derivatives reproducibly cause bacteremia at the doses utilized in this study (21,44,45) and, although a serovar Typhi ⌬aro strain was not utilized in this study, since it was ethically inappropriate, we feel these preliminary data are sufficient to suggest that the ssaV mutation was modulating the virulence of this strain, thus reducing the bloodstream survival of ZH9 and eliminating postimmunization bacteremia, which has been identified as a key safety feature in potential live oral typhoid vaccines. This would be in keeping with data from animal models demonstrating that a functional SPI-2 system is required for intracellular survival and establishment of the early bloodstream phase of serovar Typhi infection.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…There was no evidence for systemic spread of ZH9, since bacteria were not detected in the blood at any time. Serovar Typhi Ty2 aro derivatives reproducibly cause bacteremia at the doses utilized in this study (21,44,45) and, although a serovar Typhi ⌬aro strain was not utilized in this study, since it was ethically inappropriate, we feel these preliminary data are sufficient to suggest that the ssaV mutation was modulating the virulence of this strain, thus reducing the bloodstream survival of ZH9 and eliminating postimmunization bacteremia, which has been identified as a key safety feature in potential live oral typhoid vaccines. This would be in keeping with data from animal models demonstrating that a functional SPI-2 system is required for intracellular survival and establishment of the early bloodstream phase of serovar Typhi infection.…”
Section: Discussionmentioning
confidence: 93%
“…Mutant derivatives of Ty2 have been found to be less virulent than derivatives of other wild-type serovar Typhi strains containing identical mutations (21,45), and although not demonstrated conclusively, this has been attributed to the presence of an rpoS mutation in the Ty2 parent strain (6,37). The safety and immunogenicity of the Salmonella strains used here was established in preclinical murine studies with serovar Typhimurium.…”
Section: Discussionmentioning
confidence: 98%
“…In concordance, S. Typhi CVD906, a live vaccine, derived from ISP1820 with deletion mutations caused fever and other adverse reactions in humans in aroC and aroD [73], is highly immunogenic but [72,74]. This is in contrast to the S. Typhi CVD908 Ty2 ΔaroC ΔaroD vaccine strain, which did not cause any adverse effects [72].…”
Section: Vaccine Developmentmentioning
confidence: 99%
“…Indeed, new vaccines have been developed. Further, it has been found that a highly immunogenic live oral Salmonella vaccine would ideally be suited as a carrier of genes that express protective antigens cloned from other antigens (3)(4)(5) and such hybrid recombinant Salmonella vaccines are expected to invoke protective immunity against both the carrier strains as well as the foreign antigens (6). This is the basis of Salmonella vaccine vector and this review seeks to illustrate this milestone in the scientific research done to date.…”
Section: Introductionmentioning
confidence: 99%